The Influence of Political Connections on Tax Avoidance with Institutional Ownership Structure as a Moderation - Kristianto Tricahya Prabowo; Anindya Ratna Kartika Hady; Janitra Prabowo (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
This study aims to evaluate the role of ownership structure as moderating factor in the relationship between political connection and tax avoidance. Political connections are inseparable in their practices to generate business benefits for the company, especially when the company’s ownership has strong political connections with the government. The acquisition of data is based on observations of the annual reports of companies listed on the LQ 45 Indonesia Stock Exchange during 2020-2024 with SPSS as the analytical instrument. The results showed that political connections have a positive effect on tax avoidance and can be strengthened by the institutional ownership structure.